Neutrophil MiRNA-128-3p is Decreased During Active Phase of Granulomatosis with Polyangiitis - Surmiak, Marcin; Hubalewska-Mazgaj, Magdalena; Wawrzycka-Adamczyk, Katarzyna; Musial, Jacek; Sanak, Marek (Current genomics, 2015)
Granulomatosis with polyangiitis is a rare chronic inflammatory disease. In this multisystem autoimmune disorder neutrophils cause small vessels necrosis and infiltrate perivascular tissue to form granulomas. Progression of the disease is evaluated by the symptoms score and by a titer of antineutrophil cytoplasm antibodies. Despite glucocorticoid and immunosuppressive therapy, prognosis is complicated by chronic renal insufficiency, hearing loss and skin ulceration. In this preliminary study we tested the hypothesis that altered neutrophil expression of miRNAs can contribute to the cell activation, extracellular traps formation and decreased apoptosis. First we compared a profile of 728 miRNAs expressed in circulating neutrophils of patients with active disease and matched healthy donors. Subsequently, candidate miRNAs were quantified in neutrophils from 16 subjects with active disease, 16 asymptomatic patients at the remission and in 16 healthy controls. Out of 11 candidate miRNAs, only miR-128-3p was both biologically (relative quantity < 30% control or remission patients) and statistically (p<0.01) decreased in the cells during active stage of the disease. This miRNA correlated with a clinical score of the disease well. A set of 10 transcripts involved in the mechanism of the disease was quantified from the same neutrophils RNA. Relative expression of MMP9 was higher in neutrophils from the patients with active disease and correlated negatively with miR-128-3p. The opposite finding was present for MTA1 transcripts. Despite surprisingly scarce changes in the expression of neutrophil miRNAs, miR-128-3p is the best candidate for deciphering etiology of granulomatosis with polyangiitis.